Experimental Study on Methane Hydrate Dissociation by Depressurization in Porous Sediments - Lijun Xiong; Xiaosen Li; Yi Wang; Chungang Xu (Energies, 2012)
Based on currently available data from site measurements in the Shenhu Area of the South China Sea, methane hydrate dissociation behavior by depressurization is studied in a one-dimensional experimental apparatus. According to time variation of temperature, resistance and gas production, the hydrate dissociation process is divided into three stages: free gas release, rapid dissociation and gradual dissociation. The experimental results show that as the hydrate saturation increases the proportion of hydrate decomposed decreases in the rapid dissociation stage. The hydrate dissociation rate and the dissociation heat increase as the dissociation pressure decreases. Furthermore, the decrease of the dissociation pressure works against the secondary formation of the hydrate.